ETHICAL PROPOSITIONS IN THE ECOLOGICAL CONSIDERATION OF EDUCATION: ENVIRONMENTAL KNOWLEDGE? - Farias de Araújo, Angela Irene; Scur, Luciana (Revista Direito Ambiental e Sociedade, 2020)
The study aims to demonstrate the important issue of ethics in education and the need to protect the environment as a fundamental resource, especially in what is linked to the ecological and environmental issue through bibliographic research and investigation about ethics and education in the construction and reformulation of environmental knowledge.